Adjustment of Optimal Sports Site Selection Criteria for Elderly Using Analytical Hierarchy Process and Geographic Information System - Omid Jamshidi; Morteza Doostipasha; Seyed Mohamad Hosein Razavi; Mahmood Gudarzi (University of Social Welfare & Rehabilitation Sciences, 2018)
Objectives Aging and its associated problems are one of the challenges in the country. This necessitates the need for proper planning during this period. In this regard, the present study was conducted with the aim of fitting the indicators for choosing optimal sports location for the elderly. Methods & Materials The present study is a descriptive-analytic research that determined the weights of research criteria using a structured interview with eight experts in Analytical Hierarchy Process. In addition, the pools of Karaj (27 cases) were selected as the study population and the elderly people referred to these pools were selected as the research community. A total of 127 elderly were examined using stratified sampling. After weighing the sub-criteria of each research criterion, AutoCAD, Excel, ArcGIS, and Google Earth software were used to create a spatial database. Results Of the total 127 elder participants, 66% were male, 48% were aged 60-65 years, and 54% spent more than 6 hours a week on sports. According to experts’ opinions, three indicators of accessibility, proximity to other land uses, and safety ranked higher in the field of influencing the selection of sports places. Among the sub-criteria, subway lines and highways for access index; proximity to parks and green spaces and proximity to cultural centers for proximity index; and proper position to health centers and fire centers for safety index had relative importance compared to other sub-criteria.  Conclusion Proximity to other land uses and safety was recognized as important criteria influencing the selection of sports places. By using the results of this research and by correctly locating the sports venues, it is possible to prevent the mistakes in choosing the location of sports facilities.